Maintaining the Advantages of Strengthening the Islamic Religious Learning Model at SMP Negeri 22 Balikpapan - Muhammad Isnaini (SYAMIL: Journal of Islamic Education, 2023)
The learning reinforcement model plays an important role in education to improve student learning outcomes through learning models provided by educators in accordance with the plan that has been programmed in the teaching and learning process. Research objectives: To analyze and maintain the advantages of the Islamic Religious Education learning model. Data collection techniques through observation, interviews, documentation and photography. Data analysis using the Milles Huberman model. The learning models that we apply such as cooperative learning models, problem based learning models, project based learning models, discovery learning, the methods we use every one is a teacher marcet place, activities, questions and answers, demonstration, participatory and role-playing, media used using powerpoint, laptops, student package books, whiteboards and media posters related to learning materials. Efforts made by schools to overcome the shortcomings of the Islamic religious learning model are carried out by academic disciplines, especially in the field of PAI, students are more involved in the alignment model, the Project Based Learning (BJL) model uses activity as a medium that makes students more active in developing their potential for optimal learning outcomes. There are several models that we have implemented, including; Discovery Learning model, Problem Based Learning Model and Project Based Learning Model, while the learning method is applied by combining several methods; lectures, quizzes, socioderamas, card sorts, practice: in terms of media use we use hadith books, posters and package books, as well as PowerPoint in presentations.